Numerical modelling of glulam frames with buckling restrained braces. (15th July 2021) - Dong, Wenchen; Li, Minghao; Lee, Chin-Long; MacRae, Gregory
Highlights: Component-based models for glulam frames with BRBs are provided. The stiffness prediction methods for dowelled connection and screwed connection are verified. The influence of connection stiffness on the system is investigated. The effect of manufacturing tolerances on the system is discussed. Abstract: This paper presents component-based numerical models to simulate the seismic behaviour of a timber-steel hybrid structure consisting of glulam frames and buckling restrained braces (BRBs). The model is validated by existing experimental data of two full-scale BRB-braced glulam frames (BRBGFs) where dowelled connections and screwed connections were used as the critical BRB-timber interface connections, respectively. Parametric studies are also conducted by the validated model to investigate the influence of the interface connection stiffness and manufacturing tolerances on the performance of the BRBGFs. The studies showed that the interface connection relative overstrength factor γ  = 1.5 was a suitable value to engage BRBs, ensure ductile behaviour and achieve a cost-effective connection design. Manufacturing tolerances had a negligible impact on the ultimate strength and energy dissipation under cyclic loading but might affect the performance under serviceability limit state loads.